Role of the Aspartate Transaminase and Platelet Ratio Index in Assessing Hepatic Fibrosis and Liver Inflammation in Adolescent Patients with HBeAg-Positive Chronic Hepatitis B - Yu Zhijian; Li Hui; Yao Weiming; Lin Zhanzhou; Chen Zhong; Zheng Jinxin; Wang Hongyan; Deng Xiangbin; Yang Weizhi; Li Duoyun; Liu Xiaojun; Deng Qiwen (Gastroenterology Research and Practice)
This study described an index of aspartate aminotransferase-to-platelet ratio index (APRI) to assess hepatic fibrosis with limited expense and widespread availability compared to the liver biopsy in adolescent patients with CHB.